2021
DOI: 10.1158/1078-0432.ccr-20-4772
|View full text |Cite
|
Sign up to set email alerts
|

KRAS G12C Mutation Is Associated with Increased Risk of Recurrence in Surgically Resected Lung Adenocarcinoma

Abstract: Purpose: KRAS G12C is the most common KRAS mutation in primary lung adenocarcinoma (LUAD). Phase I clinical trials have demonstrated encouraging clinical activity of KRAS G12C inhibitors in the metastatic setting. We investigated disease-free survival (DFS) and tumor genomic features in patients with surgically resected KRAS G12C -mutant LUAD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 41 publications
2
34
0
1
Order By: Relevance
“…It has been shown that co-alterations of STK11/LKB1 and KEAP1 were significantly associated with lung tumors [49,63,64]. One explanation is the proximity of the corresponding genomic loci on the short arm of chromosome 19 (at 19p13.2 for KEAP1 and 19p13.3 for STK11/LKB1).…”
Section: Stk11/lkb1 Alterations Promote Lung Cancer Cell Survival And...mentioning
confidence: 99%
“…It has been shown that co-alterations of STK11/LKB1 and KEAP1 were significantly associated with lung tumors [49,63,64]. One explanation is the proximity of the corresponding genomic loci on the short arm of chromosome 19 (at 19p13.2 for KEAP1 and 19p13.3 for STK11/LKB1).…”
Section: Stk11/lkb1 Alterations Promote Lung Cancer Cell Survival And...mentioning
confidence: 99%
“…The genes included in the molecular typing of LUAD often include EGFR, ALK, ROS1, BRAF, NTRK1/2/3, MET, and RET, and the mutation rate of functional driver genes is about 60%, among which KRAS, EGFR mutations and EML4-ALK fusion is the most common driver gene, accounting for about 35% to 40% (23)(24)(25). The study by Jones et al showed that KRAS G12C mutation was associated with worse disease-free survival after complete resection of stage I-III LUAD (26).…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 Additionally, patients with specific gene mutation show worse prognosis than patients with wild‐type genotype. 42 EGFR mutation‐positive NSCLC, targeted therapy as adjuvant treatment, has improved the survival of NSCLC patients. For instance, the 24‐month DFS is 89% in osimertinib group versus 52% in the placebo group, with reduced local relapse and metastasis.…”
Section: Clinical Management Of Nsclcmentioning
confidence: 99%